(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The present work is aimed at formulation of fluvastatin SNEDDS, its optimization using Box-Behnken Design (BBD) followed by in-vitro and in-vivo evaluation. The SNEDDS formulation comprising 30% sefsol 218, 50% cremophor RH40 and 35% propylene glycol choosen optimal with maximum drug release of 98.62% when compared to pure drug (13.76 %). The formulations evaluated for physic-chemical parameters and results were found within the acceptable limits. The in vivo pharmacokinetic study conducted on Wistar rats indicate that drug plasma concentration in rats administrated with fluvastatin SNEDDS was higher than that of animals treated with fluvastatin. Cmax of the SNEDDS (699.972±2.85 ng/ml) was found significant (p<0.05) when compared to that of pure drug (225.7±0.57 ng/ml).Tmax of both fluvastatin SNEDDS and pure drug were 50±0.53 and 75±0.72 minutes. The AUC0-∞and AUC0-t of SNEDDS was higher than the pure drug indicating higher drug concentrations in blood resulting in systemic absorption of fluvastatin from developed SNEDDS.